First record of buccinid genus Chauvetia (Mollusca: Gastropoda) from the fossil record of the New World (Miocene, Venezuela) and its paleobiogeographic implications. (1st October 2015) - Landau, Bernard; da Silva, Carlos M.; Vermeij, Geerat J.
Abstract: Until now, the buccinid genus Chauvetia was considered of European or West African origin, and is still endemic to these areas today. This paper describes the oldest representative of the genus, Chauvetia inopinata nov. sp., from the upper Burdigalian-lower Langhian transition Cantaure Formation of Venezuela. This surprising record suggests a New World tropical origin to the genus and subsequent immigration to the Old World before the earliest known Old World record, which is upper Tortonian. We postulate that this pre-late Tortonian (pre-8.12–7.42 Ma) dispersal of the tropical Gatunian west-Atlantic Chauvetia into the tropical East Atlantic European-West African Province most probably happened during the 10.71–9.36 Ma interval (early–mid Tortonian) during which the Circum-Tropical Current weakened, and the northward Intra-Caribbean Current had started, enhancing the Gulf Stream and the North Atlantic Current. This new data constitutes compelling evidence of a pre-Pliocene eastward dispersal of New World shallow marine organisms across the Atlantic.